Designing themes of Biology in Teaching Science 6, General Education Curriculum 2018 to Improve Quality of Learning - Thi Phuong, Le (VNU Journal of Science: Education Research, 2021)
Theme-based teaching is becoming more focused, assisting students to see the dilemma entirely, apply knowledge critically, and explore and solve problems relevant to real life. Teachers, on the other hand, have a tough time designing themes that fulfill the curriculum's specifications. Teachers may use the 5-step process suggested in the paper with various tools to design a Biology theme by following the steps outlined in this report in teaching to teach  Science 6 in accordance with the 2018 General Education Curriculum. The findings of a pedagogical experiment indicate that the theme is relatively appropriate for students in secondary schools. Teachers praise the subject for its substance, which meets the Science curriculum's requirements.